Atmospheric transmission at microwaves (ATM) an improved model for millimeter - Pardo, J.R (IEEE Transactions on antennas and propagation)
We present a model of the longwave atmospheric spectrum that improves in many respects widely used older models such as the microwave propagation model (MPM), since it is based on broadband measurements and calculations. According to our data, the model is fully applicable from 0 to 2 THz while including lines up to 10 THz. Its primary goal is to simulate the millimeter/submillimeter region accessible from the ground (frequencies up to ~2 THz at most, with a few windows between 1 and 2 THz accessible only under exceptional conditions at very dry sites). Line-by-line calculations of the absorption are performed using a line database generated from the latest available spectroscopic constants for all relevant atmospheric species. The collisional line widths are obtained from published laboratory data. The excess of absorption in the longwave range that cannot be explained by the line spectrum is modeled by introducing two different continuum-like terms based on FTS measurements between 170 and 1100 GHz: collision-induced absorption of the dry atmosphere due to transient dipoles in symmetric molecules (N 2 and O2) and continuum-like water vapor opacity. All H2O lines up to 10 THz are included in order to correctly account for the entire H2O far-wing opacity below 2 THz for a given line-shape. Hence, this contribution does not need to be part of a pseudocontinuum term below that frequency cutoff (still necessary, as shown in this paper) in contrast to other models used to date. Phase delays near H2O and O2 resonances are also important for ground-based astronomy since they affect interferometric phase. The frequency-dependent dispersive phase delay function is formally related to the absorption line shape via the Kramers-Kronig dispersion theory, and this relation has been used for modeling those delays. Precise calculations of phase delays are essential for the future Atacama large millimeter array (ALMA) project. A software package called atmospheric transmission at microwaves (ATM) has been developed to provide the radioastronomy and aeronomy communities with an updated tool to compute the atmospheric spectrum in clear-sky conditions for various scientific applications. We use this model to provide detailed simulations of atmospheric transmission and phase dispersion for several sites suitable for submillimeter astronomy